2018
DOI: 10.1016/j.heliyon.2018.e00902
|View full text |Cite|
|
Sign up to set email alerts
|

Meningitis B vaccination: knowledge and attitudes of pediatricians and parents in Greece

Abstract: Bexsero®, a meningitis B vaccine, was recently included in the National Immunization Programme (NIP) in Greece, with restricted access to high risk groups only. To map the need to expand coverage, this study assessed pediatricians and parents' perceptions and attitudes towards meningitis B, inclusion of Bexsero® in the NIP and vaccination uptake.We analyzed data from 201 private practice pediatricians questionnaires and 1003 parents phone interviews. Both (pediatricians 64.7%, parents 88.5%) considered meningi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In the United States, studies have indicated that healthcare providers are not frequent prescribers of MenB vaccines, potentially because of a general lack of knowledge of serogroup B disease and the available vaccines as well as an inability to define official vaccination guidelines [30,31]. In Greece, where MenB vaccination is not included in the national immunization plan, pediatricians may hesitate to recommend vaccination to parents owing to high out-of-pocket costs [169]. In Spain, despite the availability of the MenB vaccine through the private market, the low national healthcare budget dedicated to vaccines may preclude the inclusion of the MenB vaccine into a publicly funded program [170].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, studies have indicated that healthcare providers are not frequent prescribers of MenB vaccines, potentially because of a general lack of knowledge of serogroup B disease and the available vaccines as well as an inability to define official vaccination guidelines [30,31]. In Greece, where MenB vaccination is not included in the national immunization plan, pediatricians may hesitate to recommend vaccination to parents owing to high out-of-pocket costs [169]. In Spain, despite the availability of the MenB vaccine through the private market, the low national healthcare budget dedicated to vaccines may preclude the inclusion of the MenB vaccine into a publicly funded program [170].…”
Section: Discussionmentioning
confidence: 99%